(untitled) (Educational Dimension, 2021)
The content of the course is considered in view of the leading function as a basis for integrating the content of professional training at the fundamental and methodological levels. In the process of developing the integration course, the degree of subject integration was taken into account (within the course); interdisciplinary (within the agreed disciplines, an important factor is to take into account the assimilation of the categorical apparatus of the industry in close connection with another (Linguistics and History), the role of the course in the system, the interaction of professional courses (in the content of the educational process). philologists provides efficiency in the formation of competencies needed to expand the understanding of linguoculturology, which determines the relationship and interaction of culture and language in their functioning and generalizes this process as a holistic structure of units in their unity of linguistic and cultural content. blocks in the structure of the course “Linguoculturology” Linguoculturology as a science and academic discipline. Discursive and pragmatic characteristics of linguistic and cultural universals. Historical and cultural descriptors of linguistic and cultural discourse. The contents of the selected thems (1.1. Ontology of linguoculturology. Relationships of linguocultural studies with other fields of knowledge. 1.2. Value communicative nature of linguocultural studies. The concept of linguoculture in the information-semiotic field of culture. 1.3. Linguistic picture of the world. Linguistic and cultural personality. 2.1. Models of the world as a historical type of culture and a cognitive-cultural scenario of personality activity. Verbalization of world models in Ukrainian and other linguistic cultures: a comparative aspect. 2.2. The concept of background knowledge. Functional and ideological components of non-equivalent and equivalent vocabulary as a mechanism of expression of ethnocultural specificity. The concept and its representation in various arts. 2.3. Paremiological representation of ethnolinguistic consciousness in Ukrainian and other linguistic cultures: a comparative aspect. 3.1. Linguoculture in the genesis of Ukrainian culture: traditions and transformations. 3.2. Religious and cultural-reflective determinants of culture. Tolerance and empathy as descriptors of the modern model of intercultural communication.) are described taking into account the principles of scientificity, continuity and consistency.